A review study on synthesis methods of AgNanoparticles, considering antibacterial property and cytotoxicity - Mudhafar, Mustafa; Zainol, Ismail; Jaafar, Che Nor Aiza; H. A., Alsailawi; Desa, Shakinaz (Dr. Yashwant Research Labs, 2021)
Silver nanoparticles (AgNP) have been used in many medical and biological applications due to their unique features and characteristics. One of the most important issues researchers address in nanoscience is finding suitable methods to produce nanoparticles with environmentally friendly and non-toxic properties. The unique chemical, physical and biological properties that AgNP possesses give that impetus to developing their production methods. In recent years, there have been many studies documented for the production of AgNP during the development of green synthesis methods (GSM). The present study describes methods for the GSM of AgNP, their biological properties, and other applications, giving the most appropriate methods to synthesize AgNP.AgNP is one of the essential metallic particles, as they can be manufactured and designed in easy ways, and they are also adjustable because they were used in many fields such as catalysts, ideal biometrics, and photo-controlled delivery Systems. AgNp is beholden as a prospectively for tissue regeneration in bioengineering due to its ability in the delivery system as an ideal gene. The studies examined in the current study demonstrated the ability of AgNP in many medical applications because they possess antibacterial properties, and their toxicity can be reduced according to the recorded reports.